A Case Series of Myocarditis Following Third (Booster) Dose of COVID-19 Vaccination: Magnetic Resonance Imaging Study - Shiyovich, Arthur; Witberg, Guy; Aviv, Yaron; Kornowski, Ran; Hamdan, Ashraf (Frontiers in Cardiovascular Medicine, 2022)
Background: Myocarditis has been reported following the first two doses of the Pfizer-BNT162b2 messenger RNA (mRNA) COVID-19 vaccination. Administration of a third dose (booster) of the vaccine was recently initiated in Israel. Objective: to describe the characteristics of patients referred for a cardiac magnetic resonance imaging (CMR) with myocarditis following the booster. Methods: Patients referred for CMR with a clinical diagnosis of myocarditis within 21 days following the booster, between July 13, and November 11, 2021, were analyzed. Results: Overall, 4 patients were included, 3/4 (75%) were males, mean age of 27±10 years. The time from the booster to onset of symptoms was 5.75±4.8 days (range 2-14). Obstructive coronary artery disease was excluded among 3 patients (75%). CMR was performed 34±15 days (range 8-47 days) following 3rd vaccination. The mean left ventricular ejection fraction was 61±7% (range 53-71%), regional wall motion abnormalities were present in one-patient. Global T1 was increased in one-patient, while focal T1 values were increased in 3-patients. Global T2 was increased in one-patient, while focal T2 values were increased in all-patients. Global ECV was increased among 3 patients, while focal in all patients. The median LGE was 4±3% (range 1-9%) with the inferolateral segment most common location (3/4 patients). All patients were positive for the Updated Lake Louise Criteria. Conclusions: Patient characteristics and CMR findings with myocarditis following the booster vaccine are relatively mild and consistent with those observed with the first two doses. Although larger scale prospective studies are necessary these initial findings are somewhat reassuring.